FrameWeb Editor: Uma Ferramenta CASE para suporte ao Método FrameWeb - Campos, Silas Louzada; Souza, Vítor E. Silva (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
The FrameWeb method defines a standard architecture to facilitate the integration with widely-used Web development frameworks, proposing a set of models that bring to architectural design the concepts inherent to these frameworks. In this paper, we present the FrameWeb Editor, a CASE tool built on top of the meta-models that define the syntax of the FrameWeb language, providing a graphical editor for the creation of valid models in this language and serving as foundation to other functionalities such as, e.g., code generation. The tool has been successfully used to model projects in the context of student course assignments, showing potential for its use in industrial settings.